Estudo das reuniões de coordenação da produção em obras - Haka, Osmar Roberto (Universidade Federal de São Carlos, 2007)
This work presents an exploratory study on the coordinating meetings, in the stage of production of the Civil Engineering in the subsector constructions, classifying the different forms of management, raising the ways of communication and identifying which are the fiscalized elements. Also will be treated the questions to the relations between the participants of the meetings, conditions for the establishment of partnerships between them and how its activities are made compatible. The planning meetings belong to the operational level, where the directions of the Production Projects and the Projects to Production, will be had, will be transmitted, if necessary adapted, made compatible and executed, propitiating a formal occasion, in which tools and techniques of management can be transmitted and be evaluated. Amongst main participants of the planning meetings, we can cite representatives of the constructors and the specialists subcontractors. The parameters raised will evidence which are the better ways of leading such meetings, in the diverse stages of production, in accordance with the constructive culture and with the technological resources of the company.
Keywords: Indústria de construção civil - administração; Canteiro de obras; Subempreiteiros; Planejamento e controle da produção; Capacidade gerencial; Compatibilização de atividades; Civil construction; Specialists subcontractors; Planning and control of the production; Management ability; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL